Disinformation and elections to the European Parliament - Annegret Bendiek; Matthias Schulze (Stiftung Wissenschaft und Politik (SWP), 2019)
Elections to the European Parliament (EP) will take place in May 2019. Politicians and experts fear that the election process might be disrupted by disinformation campaigns and cyber attacks. In December 2018, the European Commission presented an action plan against disinformation. It provided 5 million euros for raising awareness amongst voters and policymakers about manipulation, and for increasing the cyber security of electoral systems and processes. The strategy relies on voluntary and nonbinding approaches by Internet companies to fight disinformation. To protect the integrity of elections in the medium term, independent research into technical, legal and market-regulating reforms must be boosted. The objective should be to preserve the functionality of democracies and elections in the age of digitalisation.
Keywords: 320